2021
DOI: 10.6023/a21060253
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Hole Transport Materials Based on Spiro Aromatic-Skeleton in Perovskite Solar Cells

Abstract: The third-generation energy electro-optical technology, perovskite solar cells (PSCs), have risen fast over the past decade. In view of the characteristic of intrinsic-semiconductor of organic-inorganic hybrid perovskite materials, as well as the multilayer planar architecture of PSC devices, the hole transport materials (HTMs) based on organic small molecules were introduced PSCs to make up of p-type layer, by which not only full-solid state PSCs were established, but also the highly efficient and stable PSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 87 publications
0
0
0
Order By: Relevance
“…The 1 H/ 13 C NMR spectra were obtained with a Bruker Avance500 II spectrometers (Billerica, MA, USA) at ambient temperature by utilizing deuteron dimethyl sulfoxide (DMSO-d 6 ) as a solvent and tetramethylsilane (TMS) as a standard. The mass spectra were obtained with a Waters Xevo G2-XS Tof (Milford, MA, USA).…”
Section: General Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H/ 13 C NMR spectra were obtained with a Bruker Avance500 II spectrometers (Billerica, MA, USA) at ambient temperature by utilizing deuteron dimethyl sulfoxide (DMSO-d 6 ) as a solvent and tetramethylsilane (TMS) as a standard. The mass spectra were obtained with a Waters Xevo G2-XS Tof (Milford, MA, USA).…”
Section: General Methodsmentioning
confidence: 99%
“…Hence, a great deal of research works based on spiro compounds have been conducted to develop high-performance HTMs. By refining the research results, it can be found that spiro[fluorene-9,9′-xanthene] (SFX) is an ideal alternative to SBF, as the asymmetric spiro structure of SFX makes its derivatization and regulation more flexible than SBF [ 12 , 13 , 14 ]. For the electroactive units of HTMs, the electron-rich aniline-like segments are preferred because of their suitable properties, for instance, the lone pair of electrons of nitrogen atoms facilitate the formation of radical cation intermediates [ 15 ].…”
Section: Introductionmentioning
confidence: 99%